UX Evaluation Using Firstclick, Performance Measurement, RTA, And Questionnaire On E-Commerce Website - Candiasa, I Made; Gunadi, I Gede Aris; Putra, I Nyoman Wahyu Semeru (Sinkron : jurnal dan penelitian teknik informatika, 2023)
E-commerce has made transactions easier for several persons. SKI (Semadi Kwazay Indoland), a company in the real estate market, is one of the numerous organizations that develop e-commerce websites. The company wants the e-commerce website to attract a wider audience. Therefore, an evaluation is necessary to measure the usefulness of the website. Twenty responses were divided into two groups of ten: the advanced group and the novice group. The selected assessment approaches are performance measurement to evaluate the system's efficiency and error rate, first-click usability testing to evaluate the system's effectiveness, and RTA and the SUS questionnaire to evaluate user happiness. The following are the study's findings: This e-commerce website is quite efficient, as there is no significant difference in the time necessary to complete the 10 activities between the two groups of respondents. The mean participant questionnaire score for the e-commerce website was 49.75, which was much lower than the average SUS score of 68. The e-commerce website page is highly effective, as the performance measurement test results suggest a comparatively low error rate across both novice and advanced respondent groups.